The influence of value orientations to formation of image of future teacher (Pedagogy of Higher and Secondary Education, 2013)
Razmolodchikova I. V. The influence of value orientations to formation of image of future teacher.In this article authors attempt to analyze the impact of value orientations on the formation and development of personality of modern primary school teacher.
Keywords: teacher; self-development; value orientations; professional pedagogic values; culture; self-perfection